Higher Education in the Era of Global Pandemic - Dr. Anupa Singh (International Journal of Engineering and Management Research, 2020)
The impact of COVID-19 can be seen in every sphere of life. It has significantly disrupted the higher education sector as well, which a critical determinant of a country’s economic future. The higher education sector is undergoing a tectonic shift right now. The closure of colleges and universities has widespread implications for students, faculty, administrators and institutions themselves. Research on online teaching and learning is inconclusive so far as research on coronavirus. Education is not only a cognitive process but also a social process. The transition from on-campus to online teaching and learning is not easy, as there are many challenges. The COVID-19 pandemic has underscored how indispensable it is for our population to be digitally literate. It may fashion a long overdue and welcome rebirth of our education systems. The long-term sustainable triumph of this tectonic shift will depend on some major elements of online learning.COVID-19 is causing us to challenge deep rooted notions of when, where and how we deliver education, the role of colleges and universities, the importance of life-long learning and the distinction between traditional and non-traditional learners. We can expect a new and different kind of educational model to emerge from COVID-19.This paper discusses the problems faced by the higher education sector due to COVID-19.Some suggestions have also been pointed out in this paper with regard to how we can further revolutionise the teaching and learning process to improve the experience of both, the teachers and learners during the pandemic.